Macroinvertebrate diversity in a Subtropical High-Pressure Zone (SHPZ) man-made lake: Goreangab Dam, Windhoek, Namibia (Namibian Journal for Research, Science and Technology, 2022)
This research investigated the diversity and distribution of macroinvertebrate assemblages of a sub-tropical high-pressure belt man-made lake, the Goreangab Dam, in Windhoek, Namibia in order to develop a respective index of biotic integrity as a baseline of determining and monitoring the health status of the dam. Macroinvertebrates samples were collected biweekly, over a period of two months (August and September 2019) from 8 stations along the bank of the dam. Collected macroinvertebrate samples were sorted live, counted and identified to the lowest taxonomic level possible. The Shannon Weiner index (H'), Simpson’s index (D) and Pielou Evenness index (J’) were used in analysing macroinvertebrates diversity. A total of nine different macroinvertebrate species belonging to different orders were recorded during the sampling period. Chironomus plusmosus (larvae), had the highest composition (19%) and Arctocorisa arguta with the lowest composition (6%). Anthropogenic activities have a huge impact on the distributions of the macroinvertebrate assemblages according to the tolerance of water pollution. The fact that the Chironomus plusmosus (larvae) are the highest in composition shows that the waterbody is unhealthy and at this stage only supports the life of species that are tolerant to water pollution.
Keywords: Ecological modelling; Macroinvertebrate diversity; Man-made lake; Water quality